Antimicrobial Activity of Royal Jelly - M. Alreshoodi, Fahad; Sultanbawa, Yasmina (Anti-Infective Agents, 2015)
Royal jelly (RJ) is a unique secretion that is produced by the mandibular and hypopharyngeal glands of worker bees and used globally for its unique health benefits. It consists mainly of water, proteins, fatty acids, minerals, carbohydrates, vitamins, and other components. RJ as a raw and purified product has been evaluated for its bioactivity in in-vitro, animal and clinical studies and one of the most notable findings was its antimicrobial activity. Although there are many types of antibiotics that can inhibit the growth of pathogenic bacteria, antibiotic-resistant strains have emerged, leading to a search for alternative methods through the re-examination of past remedies. Certain components in RJ have shown antimicrobial effects against a wide range of microbes, including bacteria, viruses, yeast, and fungi. Trans-10- hydroxy-2-decenoic acid, Royalisin, and Jelleines are the main antimicrobial biaoctives obtained from RJ, and they have significant antibacterial potential. This review is on the antimicrobial effects of RJ and their potential use in medical and other applications.
Keywords: antimicrobial peptides